Meckel's diverticulum - Clinical presentation and pitfalls in diagnosis in the pediatric age group in Singapore - Ganakirthana Kalpenya Devi; Anne Hui Yi Goei; Kalyanasundaram Ragavendra; Xuxin Lim; Candy S C. Choo; Lin Yin Ong; Harvey James Eu-Leong Teo; Narasimhan Kannan Laksmi (Wolters Kluwer Medknow Publications, 2022)
Purpose: The purpose of this study was to study the presentation of patients who underwent Meckel's diverticulectomy (MD) and utility of pertechnetate Meckel's scan in the diagnosis of MD. Methods: The clinical presentation of a retrospective cohort of patients who underwent MD from January 2007 to December 2019 was studied. The modes of presentation, treatment, and the diagnostic utility of pertechnetate Meckel's scans were evaluated. False-positive and false-negative scans were reviewed. The presence of gastric mucosa on histology of Meckel's was correlated with presentation as gastrointestinal bleeding and positive scan results. Results: Ninety-nine patients underwent MD. Thirty-five out of 263 (13.3%) Meckel's scans done were positive. There was a male preponderance (86.9%). The peak age of presentation was 0-4 years (rectal bleeding or intestinal obstruction). Only a third of the patients with Meckel's diverticulum Meckel's had a preoperative diagnosis of Meckel's. The sensitivity/specificity of Meckel's scan was higher in patients presenting with painless rectal bleeding. Seven patients were false positive (weak tracer uptake or ectopic uptake) and five were false negative. Two patients with false-negative Meckel's scan, having gastrointestinal bleeding had gastric mucosa on histology of Meckel's. Conclusion: Meckel's diverticulum has a male predominance. Meckel's scan has a high sensitivity in the children presenting with fresh painless rectal bleeding but is of limited use in the diagnosis of Meckel's diverticulum in other forms of presentations. False-positive scans can be anticipated in the presence of weak or ectopic uptake. False-negative scans can occur even in the presence of bleeding and in spite of the presence of gastric mucosa in the Meckel's diverticulum. Laparoscopy is a useful tool in diagnosis and treatment.